Exploring the Nexus: a study of Malaysia-Bangladesh relations in the context of migrant workes, 1980-2022 - Khondaker, M Shahidul Islam; Azharudin Dali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines the genesis of the migrant workers-based relationships between Malaysia and Bangladesh that commenced in the 1980s and persists to recent days, particularly up to 2022. It provides a delineation of migration-related issues including the establishment of reciprocal relations, the commencement of labour migration to Malaysia, associate expenses, wages and remittance flow and the legitimacy of the worker’s mobility. The research further uncovers the socio-cultural constraints faced by Bangladeshi workers in Malaysia. The enduring connection between Malaysia and Bangladesh dates back to the ancient period characterised by a responsive interplay. Migrant worker issues have emerged as a pivotal aspect of their bilateral ties and were symptomatic with a new bilateral buildout with exercising diplomatic promptness after Bangladesh became an independent country. Employing the historiographic approach as a method, this study synthesises primary and secondary sources such as occasional reports, agreements, newspapers, books and articles. The findings present an empirical account and factual illustration of the reciprocal relationships and their constraints concerning the migration process, financial transactions and legalities of movement. The insights derived from this research would be the source for the policymakers and diplomats enabling them to reshape strategies in light of these perspectives. Additionally, this research paves the way for further studies by addressing gaps in the existing literature on Malaysia-Bangladesh relations.